Pengaruh Motivasi Internal, Praktik Pelatihan, Dan Praktik Kompensasi Terhadap Kinerja Karyawan Melalui Employee Engagement Sebagai Variabel Mediasi - Muchammad Arifhidayat; Sidiq Permono Nugroho (IQTISHADequity jurnal MANAJEMEN, 2023)
As the times progress and the population increases, the demand for employment will continue to grow and the workforce is required to have adaptable skills and qualified expertise, but sometimes the demand for the expertise of these employees is not matched by adequate training and facilities to produce the quality of human resources needed. The purpose of this study is to analyse the effect of internal motivation, training practices, and compensation practices on employee performance through employee engagement as a mediating variable. This research methodology uses quantitative research. This research population is employees of the Regional Office of the Directorate General of Taxes Central Java II. The sampling technique is purposive sampling. The sample in this study were employee respondents of the Regional Office of the Directorate General of Taxes in Central Java II.  This research data analysis uses the SmartPLS application (v.3.2.9). The results of this study are Employee Engagement has a significant effect on employee performance. Internal motivation has a significant effect on Employee Engagement. Internal motivation and training practices have an insignificant effect on employee performance. Training practices have an insignificant effect on Employee Engagement. Compensation practices have an insignificant effect on employee performance. Compensation practices have an insignificant effect on Employee Engagement. Internal motivation has a significant effect on employee performance with Employee Engagement as mediation. Training practices and compensation practices have an insignificant effect on employee performance with Employee Engagement as mediation.